Project HALTapresyon. - HyperTEAMsion; Arbado, Pearl Joy C.; Laurente, Inna Grace R.; Loberiza, Lamont Joseph S.; Militar, Anna Raisa G.; Quidato, Juin Pretzel E.; Ong, Meghan Y.; Salada, Anna Patriz F.; Salcedo, Yehonathan Joseph V. (2019.)
The World Health Organization has deemed hypertension to be a global public health issue. In the Philippines, 25% of the adults who are 21 years and above have high blood pressure (2014). HALTapresyon is a project that aimed to prevents and manage hypertension in Barangay Igtalongon, Igbaras, by (1) increasing the knowledge, awareness, and practices (KAP) regarding hypertension by 15%, (2) increasing KAP regarding physical activity by 15%, (3) increasing the KAP regarding nutrition by 20%, and (4) manage the blood pressure of hypertensive patients. The establishment of a core group and the passing of a resolution were done on order to ensure the sustainability of the project. HyperTEAMsion was also able to donate 6 blood pressure apparatuses for the continuation of the weekly blood pressure monitoring. The project implemented a series of lectures that focused on three aspects: basic knowledge, physical activity, and nutrition, whice were identified as factors that greatly affect the development and progression of the hypertension. Activities, such as DASH TAH!, Blood Pressure Moni-training, and the use of a journal, offered a more hands-on approach on educating and improving the practices of the residents. Information, education, and communication materials were also distributed to hypertensives alike. Post assessment mean scores for KAP on General Information, Physical Activity, and Nutrition, improved by 16.81%, 15.96%, and 29.70% respectively, all showing a statistical difference. For the non-hypertensives, there was a 36.94% increase in KAP. Weekly monitoring was done in relation to the management of blood pressure and it showed that 77.03% of the hypertensive individuals decreased or maintained their blood pressure. Therefore, Project HALTaspresyon could be used on the prevention and management of hypertension.
Community Project (Undergraduate, Bachelor of Science in Public Health) College of Arts and Sciences, University of the Philippines, Miagao, Iloilo. 2019.
Keywords: Hypertension -- Research